(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Of the numerous environmental factors affecting tree growth, the relationship between site quality and tree growth seems to be the most important. In this work, the production of fir wood (Abies borisii-regis Mattf.) on quantitative and qualitative basis was investigated in relation to three different site qualities (II, III, IV) at the University forest of Pertouli-Trikala, Greece. For the grading of round timber produced from 268 fir trees, the EN 1927-1:2008 CEN standard was employed. The results showed that the site quality has an influence on both quantitative and qualitative production of fir wood. Higher production and better quality of fir wood were found to be produced in the site quality II, while in the site quality IV, the quantity and quality of wood produced were less and inferior, respectively. In the site quality III, the production and quality of fir wood were at intermediate level.